(untitled) (Research, Society and Development, 2020)
The COVID-19 pandemic produced a series of changes in people’s experiences. Anchored in measures to protect against contagion, these changes have produced or distanced human relationships, as a work, leisure and culture activities, among others. Each subject experiences these changes in some way, especially young university students who have an academic and social routine. From this perspective, this work consists of an opinion paper with the objective of describing the opinion of university students from Teresina-PI in relation to social isolation and the impact generated by the pandemic on economic, social, family and health factors. For this purpose, the construction of conversation circles using virtual platforms with young people aged 20 to 28 years, of varied genres and belonging to the city of Teresina / PI, was defined as a method. The results point to damage to young people’s mental health, due to social isolation, causing distance from bonds of relevant people from their social life. At the same time, this measure has given new meaning to family ties and new forms of teaching and learning. In addition, these engines are needed to deal with the consequences of the pandemic, such as reduced income and changes in daily routines and activities. It concludes by alerting the need to evaluate the wide power of prejudice caused by COVID-19, awakening in this youth consequences that pass through the physiological barriers.